The Healing Effect of Cuttlefish Bone on Fractured Bone in Rat Model - Kloping, Laskar Pradnyan; Purwati, P.; Edward, Mouli (BALI MEDICAL JOURNAL, 2016)
Background: Fractured bone healing requires three to nine months, which prolongs the patients’ morbidity. Long bone fracture is considered to be difficult due to the dependence of bodily mobility and freedom. Bone tissue engineering materials includes hydroxyapatite (HAp), titanium, alumina, and polymers. HAp is found to be heavily abundant in cuttlefish. This study is conducted to prove that the cuttlebone has an effect of accelerating the fractured long bone healing process. Methods: This is an experimental study using a total of 32 samples of Rattus norwegicus. The Treatment Group received the cuttlebone extract + 0.9% NaCl while the Control Group received only NaCL 0.9%. Both groups were fractured beforehand. On the 14th day the fractured area was harvested and assigned for histopathology and radiographic exam. Results: The Treatment Group was found to have thicker callus formation and more osteoblasts. Conclusions: The cuttlebone extract application caused thicker callus and higher osteoblast production, proving an accelerated fractured bone healing process.
Keywords: cuttlebone, fracture, long bone, Rattus norwegicus, callus, osteoblast.